2018
DOI: 10.1021/acsami.7b14193
|View full text |Cite
|
Sign up to set email alerts
|

Smart Self-Assembled Nanosystem Based on Water-Soluble Pillararene and Rare-Earth-Doped Upconversion Nanoparticles for pH-Responsive Drug Delivery

Abstract: Exploring novel drug delivery systems with good stability and new structure to integrate pillararene and upconversion nanoparticles (UCNPs) into one system continues to be an important challenge. Herein, we report a novel preparation of a supramolecular upconversion nanosystem via the host-guest complexation based on carboxylate-based pillar[5]arene (WP5) and 15-carboxy-N,N,N-trialkylpentadecan-1-ammonium bromide (1)-functionalized UCNPs to produce WP5⊃1-UCNPs that can be loaded with the chemotherapeutic drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(55 citation statements)
references
References 64 publications
0
55
0
Order By: Relevance
“…[ 27 ] Li et al demonstrated the multifunctional application of pillar[5]arene (WP5), 15‐carboxy‐ N , N , N ‐trialkylpentadecan‐1‐ammonium bromide 1) and DOX‐conjugated UCNPs in pH‐responsive drug delivery and bio‐imaging to achieve cancer theranostics. [ 28 ] In summary, reports by several groups have demonstrated the modification of UCNPs toward pH‐responsive drug delivery systems (DDS) that can be used in cancer theranostics.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…[ 27 ] Li et al demonstrated the multifunctional application of pillar[5]arene (WP5), 15‐carboxy‐ N , N , N ‐trialkylpentadecan‐1‐ammonium bromide 1) and DOX‐conjugated UCNPs in pH‐responsive drug delivery and bio‐imaging to achieve cancer theranostics. [ 28 ] In summary, reports by several groups have demonstrated the modification of UCNPs toward pH‐responsive drug delivery systems (DDS) that can be used in cancer theranostics.…”
Section: Strategies For Targeting the Tmementioning
confidence: 99%
“…Recently, Sun et al. outlined the design of a pH‐responsive DDS (WP5⊃1‐UCNPs) for imaging‐guided chemotherapy by integrating upconversion nanoparticles (NaYF 4 :Yb/Er@NaGdF 4 ) and pillararene (WP5) into one nanosystem . This DDS shows favorable water stability, biocompatibility, drug delivery, and imaging properties.…”
Section: Cancer Therapy Based On Polymer‐decorated Transition‐metal Nmentioning
confidence: 99%
“…30,31 The electron-rich cavity and possible chemical modification on the upper and lower rims of P[n]A can provide very useful water-soluble macrocycles with hydrophobic voids. 32 Thus, anionic and cationic watersoluble pillar[n]arenes have been widely explored as hosts for chemotherapeutic drugs 33,34 as well as micelles, 35,36 vesicles, [36][37][38][39][40][41] and gatekeepers in nanovalve systems. [42][43][44][45][46][47] To the best of our knowledge, the combination of watersoluble carboxylate-substituted pillar [5]arene (CP [5]A) grafted onto SPIONs as an AMF stimuli-responsive nanodevice for drug delivery has not been described in the literature.…”
Section: Introductionmentioning
confidence: 99%